Morphological and molecular description of a novel species of Eimeria (Apicomplexa) that infects extraintestinal tissues of kiwi (Aves: Apteryx spp.) - Scheltema E; Morgan K; Singh P; Adlington B; Howe L (Springer Nature, Heidelberg, Germany, 2025)
Coccidia (Apiconmplexa) are naturally occurring and occasionally detrimental parasites of kiwi (Apteryx spp.), a unique, flightless bird species dependent upon conservation efforts for survival. Using morphological and molecular data, a new coccidia species, Eimeria koka n. sp., isolated from two closely related but geographically isolated kiwi host species, Apteryx rowi Tennyson et al. (rowi) and Apteryx mantelli Bartlett (North Island brown kiwi), is described. Oocysts are oval (20.8 × 15.9 μm) with a mean L/W ratio of 1.3, and a distinctive rough, crenellated brown oocyst wall (mean 1.2 μm), an oocyst residuum, 1–2 polar granules, and no micropyle. Sporocysts are ellipsoidal (11.6 × 6.3 μm) with a Stieda body and sporocyst residuum. Phylogenetic analysis of the cytochrome C oxidase subunit 1 (CO1) placed E. koka n. sp. in a separate clade to other Eimeria species previously identified from kiwi (Coker et al., Syst Parasitol 100(3):269–281, 2023). Comparison of DNA from oocysts with infected tissues from a single juvenile North Island brown kiwi confirmed parasitism of the kidney and lung tissues. This is the first Eimeria species identified from extraintestinal tissues in kiwi. Further molecular studies are recommended to determine the tissue distribution of E. kokan. sp. and other Eimeria species in kiwi.